Chemical potential and free energy of nanoconfined water in Newton black films - Di Napoli, Solange Mariel (Elsevier Science, 2018)
Fil: Di Napoli, Solange Mariel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina